2019
DOI: 10.1128/aac.00207-19
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evolution of Reduced Susceptibility against a Balanced Dual-Targeting Antibiotic through Stepping-Stone Mutations

Abstract: Multitargeting antibiotics, i.e., single compounds capable of inhibiting two or more bacterial targets, are generally considered to be a promising therapeutic strategy against resistance evolution. The rationale for this theory is that multitargeting antibiotics demand the simultaneous acquisition of multiple mutations at their respective target genes to achieve significant resistance. The theory presumes that individual mutations provide little or no benefit to the bacterial host. Here, we propose that such i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 76 publications
(90 reference statements)
3
34
0
Order By: Relevance
“…The frequency-of-resistance assays have indicated that spontaneous resistance evolution to ULD1 and ULD2 is rare and is responsible for only a modest decrease in compound susceptibility of S. aureus. However, a prior study suggests that combination of multiple, specific mutations at all drug targets, in the long run, can eventually render even multitargeting antibiotics ineffective [8]. To test this possibility, we have repeated the frequency-of-resistance assays with PLOS BIOLOGY 2 ULD1-resistant S. aureus VISA laboratory isolates, both of which carried a single mutation at GyrB, the primary target of ULD1/ULD2.…”
Section: Resistance Induced By Mutations At Both Target Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…The frequency-of-resistance assays have indicated that spontaneous resistance evolution to ULD1 and ULD2 is rare and is responsible for only a modest decrease in compound susceptibility of S. aureus. However, a prior study suggests that combination of multiple, specific mutations at all drug targets, in the long run, can eventually render even multitargeting antibiotics ineffective [8]. To test this possibility, we have repeated the frequency-of-resistance assays with PLOS BIOLOGY 2 ULD1-resistant S. aureus VISA laboratory isolates, both of which carried a single mutation at GyrB, the primary target of ULD1/ULD2.…”
Section: Resistance Induced By Mutations At Both Target Proteinsmentioning
confidence: 99%
“…To this aim, we have initiated adaptive laboratory evolution experiments under ULD1, ULD2, and novobiocin stresses against VISA. We have employed a previously established protocol that aims to maximize the level of drug resistance in the evolving bacterial populations [8,55]. To accurately assess potential resistance mechanisms, 10 parallel evolving populations have been exposed to gradually increasing concentrations of each compound.…”
Section: Evolution Of Resistance Under Long-term Antibiotic Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…By playing with a stringent expression system for rec2 , applying multiple cycles of recombinase production/ oligonucleotide transformation and reversibly inhibiting the MMR system during a limited time window we report below high-fidelity recombination frequencies that approach those achieved with the archetypal Red-based system (Datsenko and Wanner, 2000). This opens genome-editing possibilities in this environmental bacterium that were thus far limited to strains of E. coli , closely related enteric species (Nyerges et al, 2018; Szili et al, 2019) and some lactic acid bacteria (van Pijkeren et al, 2012).…”
Section: Introductionmentioning
confidence: 99%